2016
DOI: 10.1093/aobpla/plw081
|View full text |Cite
|
Sign up to set email alerts
|

Ecological disequilibrium drives insect pest and pathogen accumulation in non-native trees

Abstract: Non-native plant invasions represent ecological disequilibrium situations, that is, the immediate breakdown of historically co-evolved interactions once introduced into novel environments. Globalization has led to increased transfer in organisms between countries. Native enemies also undergo host expansions onto non-native plants. Ecological disequilibrium conditions can thus be expected to change unpredictably over time. By retrospectively analysing the insect pest and pathogen accumulation on established non… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
48
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 39 publications
(48 citation statements)
references
References 110 publications
0
48
0
Order By: Relevance
“…; Flory & Clay ; Crous et al . ). Depending on these alternative ecological and evolutionary scenarios, we would expect a relationship between invasion age and the impacts of allelopathy – but how this relationship changes depends on which mechanism predominates.…”
Section: Allelopathymentioning
confidence: 97%
See 1 more Smart Citation
“…; Flory & Clay ; Crous et al . ). Depending on these alternative ecological and evolutionary scenarios, we would expect a relationship between invasion age and the impacts of allelopathy – but how this relationship changes depends on which mechanism predominates.…”
Section: Allelopathymentioning
confidence: 97%
“…Lankau et al (2009) found that older populations of A. petiolata had evolved reduced production of glucosinolates, presumably due to a switch from interspecific to intraspecific plant competition. On the other hand, pressure from pathogens and herbivores could cause allelochemical production to increase over invasion age, where newer invasions may have reduced investment in defense compounds because of enemy release in their introduced range (Blossey & Notzold 1995), and older invasions may produce more defensive compounds because of accumulating pathogens and herbivores (Mitchell et al 2010;Flory & Clay 2013;Crous et al 2017). Depending on these alternative ecological and evolutionary scenarios, we would expect a relationship between invasion age and the impacts of allelopathybut how this relationship changes depends on which mechanism predominates.…”
Section: Allelopathymentioning
confidence: 99%
“…For widely established invasive plants, for example, interactions with resident and native herbivores and pathogens are expected to accumulate over time (e.g. Crous et al 2017;Stricker et al 2016), and the evolutionary component of such interactions has now been demonstrated in many cases (e.g. Strauss et al 2006).…”
Section: Eco-evolutionary Experience and Biological Invasionsmentioning
confidence: 99%
“…For example, the best-known pathogens of plantation forestry trees in the SH belong to the Teratosphaeriaceae and Mycosphaerellaceae (Hunter et al 2011). They have been moved globally with their hosts or caught up after initial establishment (Crous et al 2016), and can often cause severe disease problems in plantations. Dothistroma needle blight of pines can be a devastating disease in SH plantations following introduction, but there is no evidence of host shifts onto native gymnosperms (Barnes et al 2004).…”
Section: Multiple Fungal Associates: the Hidden Threats Of Tree Invasmentioning
confidence: 99%
“…However, pathogens usually catch-up to their hosts over time (Crous et al 2016). Additionally, native pathogens can eventually move onto the introduced trees.…”
Section: Fungal Associates and Tree Invasion Successmentioning
confidence: 99%